Fixation performance of an ultrasonically fused, bioresorbable osteosynthesis implant: A biomechanical and biocompatibility study. Issue 1 (10th February 2015) - Augat, P.; Robioneck, P. B.; Abdulazim, A.; Wipf, F.; Lips, K. S.; Alt, V.; Schnettler, R.; Heiss, C.
Abstract: Bioresorbable implants may serve as an alternative option for the fixation of bone fractures. Because of their minor inherent mechanical properties and insufficient anchorage within bone bioresorbable implants have so far been limited to mechanically nondemanding fracture types. By briefly liquefying the surface of the biomaterial during insertion, bioresorbable implants can be ultrasonically fused with bone to improve their mechanical fixation. The objective of this study was to investigate the biomechanical fixation performance and in vivo biocompatibility of an ultrasonically fused bioresorbable polymeric pin (SonicPin). First, we biomechanically compared the fused pin with press fitted metallic and bioresorbable polymeric implants for quasi‐static and fatigue strength under shear and tensile loading in a polyurethane foam model. Second, fused implants were inserted into cancellous bovine bone and tested biomechanically to verify the reproducibility of their fusion behavior. Finally, the fused pins were tested in a lapine model of femoral condyle osteotomies and were histologically examined by light and transmission electron microscopy. While comparable under static shear loads, fixation performance of ultrasonically fused pins was significantly ( p = 0.001) stronger under tensile loading than press fit implants and showed no pull‐out. Both bioresorbable implants withstood comparable fatigue shear strength, but less than the K‐wire. In bovine bone the ultrasonic fusion process worked highly reproducible and provided consistent mechanical fixation. In vivo, the polymeric pin produced no notable foreign body reactions or resorption layers. Ultrasonic fusion of polymeric pins achieved adequate and consistent mechanical fixation with high reproducibility and exhibits good short‐term resorption and biocompatibility. © 2015 Wiley Periodicals, Inc. J Biomed Mater Res Part B: Appl Biomater, 104B: 170–179, 2016.